2006
DOI: 10.1002/tcr.20080
|View full text |Cite
|
Sign up to set email alerts
|

Silsesquioxane‐based nanocomposite dendrimers with photo‐luminescent and charge transport properties

Abstract: The synthesis and characterization of octavinylsilsesquioxane (OVS)-based nanocomposite dendrimers with luminescent and charge transport properties are reported. The nanocomposite dendrimers were prepared in high yield using mild Heck chemistry of mono-haloaromatic compounds with the peripheral vinylsilane groups of OVS. Attachment of 2-naphthalene, 2-(9,9-dimethyl)fluorene, and 2-(4-phenyl)-5-(1-naphthyl)-1,3,4-oxadiazole resulted in materials with blue-violet emission (360-380 nm) and photo-luminescent quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
59
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 30 publications
1
59
0
Order By: Relevance
“…To circumvent these limitations, several research groups have focused on the modification of aryl-functionalized POSS compounds. For example, Sellinger et al functionalized vinyl 8 Si 8 O 12 with aromatic photo-luminescent compounds via Heck coupling [18,19]. Laine et al reported the synthesis of (para-iodophenyl) 8 Si 8 O 12 as a platform for coupling additional organic moieties to POSS cages [20].…”
Section: Introductionmentioning
confidence: 98%
“…To circumvent these limitations, several research groups have focused on the modification of aryl-functionalized POSS compounds. For example, Sellinger et al functionalized vinyl 8 Si 8 O 12 with aromatic photo-luminescent compounds via Heck coupling [18,19]. Laine et al reported the synthesis of (para-iodophenyl) 8 Si 8 O 12 as a platform for coupling additional organic moieties to POSS cages [20].…”
Section: Introductionmentioning
confidence: 98%
“…OVS has also been used to prepare hybrid porous polymers through various methods such as free radical polymerization, the Heck reaction, and the Friedel–Crafts reaction . The introduction of rigid and bulky cage units into luminescent molecules can inhibit aggregation and improve the fluorescence quantum efficiency . For example, Laine et al.…”
Section: Introductionmentioning
confidence: 99%
“…8 It has been found that the conjugation of alkenyl groups with the pyrenyl moiety strongly influences the electronic structure and luminescent properties of such compounds. [12][13][14][15] In this paper we present a preliminary report on a simple, efficient, atom-and stepeconomical route to alkenylpyrenes having an ester group at the alkenyl group (pyrenyl acrylates) based on dehydrogenative alkenylation (dehydrogenative Heck reaction, i.e. [12][13][14][15] In this paper we present a preliminary report on a simple, efficient, atom-and stepeconomical route to alkenylpyrenes having an ester group at the alkenyl group (pyrenyl acrylates) based on dehydrogenative alkenylation (dehydrogenative Heck reaction, i.e.…”
mentioning
confidence: 99%